Spectral and photophysical properties of phenalenone dyes in aliphatic polyurethane matrix - Bezrodnyi, V.I.; Stratilat, M.C.; Kosyanchuk, L.F.; Negriyko, A.M.; Klishevich, G.V.; Todosiichuk, T.T. (Functional Materials, 2015)
bstract:

Spectral and photophysical properties of several phenalenone dyes were investigated in dependence on the type of polyurethane polymer matrix. The increase in polarity of the solid-state medium was shown to shift absorption and luminescence to the low energy side. Structural effects of the substituents in the phenalenone chromophore on the Stokes shift value were studied. Photophysical properties of phenalenones were found out to be significantly dependent on polymerization method of the polymer matrices. Considerable growth in photostability of the organic dyes was obtained under their covalent bonding with the polymer chain.